Solving parabolic equations by Olayiwola’s generalized polynomial approximation method - Olayiwola*†, R.O. (International Journal of Mathematical Analysis and Modelling, 2023)
Polynomial approximation methods are in wide use today for approximately solving partial differential equations of mathematical physics. An evolution of the polynomial approximation methods has led to the development of Olayiwola’s generalized polynomial approximation method (OGPAM) presented in this paper, which can be applied to solve parabolic equations with constant or variable coefficients in the cases of considering slab, cylindrical or spherical geometries. Different examples have been solved using the OGPAM. The result of the present analysis has been compared with earlier analytical results. A good agreement has been obtained between the present prediction and the available results.